2008
DOI: 10.1111/j.1600-0668.2007.00509.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in personal exposures to particulate matter and carbon monoxide as a result of the installation of a Patsari improved cook stove in Michoacan Mexico

Abstract: Installation of improved cookstoves may result in significant reductions in indoor concentrations of carbon monoxide and fine particulate matter (PM(2.5)), with concurrent but lower reductions in personal exposures. Significant errors may result if reductions in kitchen concentrations are used as a proxy for personal exposure reductions when evaluating stove interventions in epidemiological investigations. Similarly, time microenvironment activity models in these rural homes do not provide robust estimates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
2
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(69 citation statements)
references
References 19 publications
(32 reference statements)
2
63
2
2
Order By: Relevance
“…The indoor PM 2.5 levels observed in this study are similar to those observed for other improved biomass stoves, including wood-and dung-burning cookstoves in India (Chengappa et al 2007;Dutta et al 2007), wood-burning cookstoves in Mexico (Masera et al 2007), and wood-burning cookstoves in Guatemala (Naeher et al 2000;Albalak et al 2001;McCracken et al 2007). In addition, Cynthia et al (2008) suggest that the relationship between reductions in kitchen concentrations and reductions in personal concentrations are not consistent and may differ based on stove type. In this study, personal carbon monoxide concentrations were not assessed which may limit interpretation of results if carbon monoxide is the health-damaging pollutant and if changes in indoor carbon monoxide do not reflect changes in personal carbon monoxide.…”
Section: Discussionmentioning
confidence: 93%
“…The indoor PM 2.5 levels observed in this study are similar to those observed for other improved biomass stoves, including wood-and dung-burning cookstoves in India (Chengappa et al 2007;Dutta et al 2007), wood-burning cookstoves in Mexico (Masera et al 2007), and wood-burning cookstoves in Guatemala (Naeher et al 2000;Albalak et al 2001;McCracken et al 2007). In addition, Cynthia et al (2008) suggest that the relationship between reductions in kitchen concentrations and reductions in personal concentrations are not consistent and may differ based on stove type. In this study, personal carbon monoxide concentrations were not assessed which may limit interpretation of results if carbon monoxide is the health-damaging pollutant and if changes in indoor carbon monoxide do not reflect changes in personal carbon monoxide.…”
Section: Discussionmentioning
confidence: 93%
“…Although these costs are much more variable on a projectby-project basis depending on stove promotion efforts and monitoring and verification strategies, incorporating a conservative minimum adoption rate of 60% within a community and monitoring costs from the Patsari Project increased costs to ∼$8 per tCO 2 -e saving. Even if these costs were three times higher, they would still be considerably less expensive than the lower range of CO 2 (25) indicate CO 2 -capture from coal plants ($25-40) and solar power ($57-240) in the United States would be 3-5 and 7-30 times more expensive than Patsari dissemination. Should stripping CO 2 from the atmosphere be required, at a cost of $140-250 per tCO 2 removed, this would be 17-31-fold more expensive than reducing CO 2 -e emissions with improved stoves.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional assessment methods are also invasive and costly, requiring installation of vented hoods in homes while using sophisticated instrumentation, and typically provide only short-term estimates of emissions for a single meal event. Second, although in more commercial sectors direct reporting or fuel inventories are used to asses fuel consumption, cookstoves often rely on noncommercial or locally purchased fuels, and tracking of fuel consumption presents methodological and logistic challenges (2). Third, for biomass burning stoves, the tools to consistently estimate the fraction of nonrenewable biomass (fNRB) harvesting have been lacking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there have been many studies of indoor air quality in developing countries, including some comparing IAQ before and after stove improvements [e.g., [27][28][29][30], few studies have simultaneously examined effects on human health. Notably, Guatemalan women reported fewer headache and less eye discomfort after installation of improved wood burning stoves [31] while the use of cleaner household fuels coincided with a 31% decrease in childhood mortality in subSaharan Africa [32].…”
Section: Respiratory Healthmentioning
confidence: 99%